Makyung the mystical heritage of Malaysia - Rahimidin Zahari 1968-; Sutung Umar Rs; Alphonsus, Cecelia (Institut Terjemahan Negara Malaysia, 2011)
Conferred the Masterpiece of the Oral & Intangible Heritage of Humanity award in 2005 by UNESCO, Malaysia's Makyung is a veritable feast for the senses. A traditional dance theatre offering a sensory mosaic of gestures, singing, music and dancing, Makyung is a living inheritance that is without doubt experiencing a revival as it enchants audiences worldwide. From the narrative gift to the verbal wit of its actors, a Makyung performance constantly evolves. Although there is no script, the improvisations enthrall audiences to return for more.